KAJIAN PEMBUATAN ARANG AKTIF BERBAHAN BAKU BAGAS TEBU MELALUI KOMBINASI PROSES KARBONISASI HIDROTERMAL DAN AKTIVASI KIMIA - Nyimas Dewi Sartika, E.Gumbira Sa'id, Machfud, Titi Candra Sunarti,Gustan Pari TIP (Jurnal Teknologi Industri Pertanian, 2014)
ABSTRACT   Sugarcane bagasse-based activated carbon which has high adsorption capacity of color in icroporous and mesoporous size in solution phase was produced through combination of hydrothermal carbonization (HTC) and chemical activation processes using phosphoric acid as  an activating agent.  The activated carbon which was obtained from HTC process at 250° C for 9 hours, followed by chemical activation process at 750° C for 90 minutes with an  impregnation  ratio of 10%  (weight  ratio of phosphoric acid  to hydrochar) has a BET surface area of 903.47 m2/g, a total pore volume of 0.597 cm3/g (volume composition: 63.32% of micropores and 36.68 % of meso-macropores), an iodine number of 951.99 mg/g, and a methylene blue number of 170.40 mg/g.  The FTIR analysis  indicated  the presence of an aromatic group and a polarity character in  the activated carbon produced.  The XRD analysis revealed  that the activated carbon had  hexagonal crystallite and mesoporous surface structures. The SEM analysis showed that the surface topography of the activated carbon had an average pore diameter between 3-10 μm. Keywords: activated carbon, sugarcane bagasse, hydrothermal carbonization, chemical   activation